Microorganisms Resistant to Free-Living Amoebae - Greub, Gilbert (American Society for Microbiology, 2004)
Free-living amoebae feed on bacteria, fungi, and algae. However, some microorganisms have evolved to become resistant to these protists. These amoeba-resistant microorganisms include established pathogens, such as Cryptococcus neoformans, Legionella spp., Chlamydophila pneumoniae, Mycobacterium avium, Listeria monocytogenes, Pseudomonas aeruginosa, and Francisella tularensis, and emerging pathogens, such as Bosea spp., Simkania negevensis, Parachlamydia acanthamoebae, and Legionella-like amoebal pathogens. Some of these amoeba-resistant bacteria (ARB) are lytic for their amoebal host, while others are considered endosymbionts, since a stable host-parasite ratio is maintained. Free-living amoebae represent an important reservoir of ARB and may, while encysted, protect the internalized bacteria from chlorine and other biocides. Free-living amoebae may act as a Trojan horse, bringing hidden ARB within the human “Troy,” and may produce vesicles filled with ARB, increasing their transmission potential. Free-living amoebae may also play a role in the selection of virulence traits and in adaptation to survival in macrophages. Thus, intra-amoebal growth was found to enhance virulence, and similar mechanisms seem to be implicated in the survival of ARB in response to both amoebae and macrophages. Moreover, free-living amoebae represent a useful tool for the culture of some intracellular bacteria and new bacterial species that might be potential emerging pathogens.